Social Security's Five OASI Inflation Indexing Problems - Michael C. Lovell (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
This paper examines five problems with the indexing procedures used by the Social Security Administration of the United States in taking inflation into account when calculating Old Age and Survivor Insurance (OASI) Benefits. Because of the commin-gling of unindexed with indexed earnings, a retiree born in 1930 who continued in a high earning career until age 75 receives an annual benefit more than 1,800 larger than would have been generated with full indexing. While the inflation indexing problems identified in this paper do not attract much attention in normal times, they can contribute to serious short-run financial instability for the OASI trust fund in periods of substantial inflation or deflation. They make the percentage increase in your inflation adjusted (CPI-W) benefit if you elect to postpone retirement and the start of OASI benefits depend in part on the pace of inflation. This paper explains how these problems could be resolved in a way that would not hurt and might help resolve Social Security's longrun solvency problems.
Keywords: H55; E31; 330; Social security; inflation; indexing; Gesetzliche Rentenversicherung; Alterssicherung; Inflation; Indexierung; USA